Parestesia Expert System! Expert System To Detect Paresthesia (Parestesia Expert System! Sistem Pakar Untuk Mendeteksi Penyakit Parestesia) - Yonky Pernando (Jurnal KomtekInfo, 2020)
Paresthesia is a condition where the sensation on the skin is abnormal, such as tingling, itching or numbness, for no apparent reason. This condition can occur only temporarily or for a long time (chronic). Bucharestesia can be temporary (temporary) or chronic. Almost everyone has experienced temporary paresthesia. This sensation occurs when nerves are accidentally compressed in certain body positions, such as sitting cross-legged for too long or sleeping with your head on your hands. Temporary paraesthesia will go away on its own when the pressure on the nerves is relieved. However, if the tingling feeling persists even though the pressure has been relieved, then there may be another disease or disorder in the body that is the cause. Chronic paresthesia is often a symptom of a neurological disease or caused by trauma to the nerve tissue. A variety of diseases can cause chronic paresthesia including vitamin deficiency, neurological disorders due to repetitive movements or other diseases. Chronic paraesthesia requires medication and management to heal. However, sometimes chronic paresthesia cannot completely heal even after undergoing treatment even though an expert system is a computer-based system that uses knowledge, facts, and reasoning techniques to solve problems that usually only one person can solve. Expert systems also help their activities as highly experienced assistants. Expert systems can also provide analysis of problems and can also recommend to users some actions to make improvements.